Orthogonal Analysis and Numerical Simulation of Rock Mechanics Parameters in Stress Field of Shaft Heading Face - Liyun Yang; Siyu Chen; Pengxiang Dong; Qingcheng Wang; Chen Huang (Advances in Materials Science and Engineering)
This paper focuses on improving the blasting effect of the drilling and blasting method in the deep rock mass and solves the problems of blasthole collapse and misfire accident in the process of drilling and blasting construction of heading face. FEM software, ABAQUS, is used to simulate the stress distribution around the blasthole by extending a certain depth in the vertical direction of the shaft heading face. The sensitivity of different depths, different heading face sizes, and different lithologies on the horizontal stress distribution is analyzed by using a six-factor four-level orthogonal analysis method. The results show that the change of the radius of the heading face has the most considerable influence on the distance of the distressed zone and the stress concentration zone, followed by the lithology and the excavation depth. Also, the excavation depth has the most significant influence on the peak stress value. Through the industrial field experiment, the in situ stress of the shaft heading face is tested, and the numerical simulation results are consistent with the field monitoring results. The results reveal the law of stress distribution near the heading face, which can provide some reference for the design of blasthole depth in the drilling and blasting construction scheme.